(untitled) (Research, Society and Development, 2022)
Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) is an economically relevant species of fruit fly and is widely distributed in Brazil. The objective of this study was to evaluate the pathogenicity of the isolate Metarhizium anisopliae (Metsch.) Sorokin (CPAFAP-3.8) against immature and adult A. fraterculus in the laboratory. Four treatments were used: isolated from M. anisopliae in sterile soil and in non-sterile soil, and control in sterile soil and in non-sterile soil. After application of the suspensions of each treatment, 3rd instar larvae of A. fraterculus were placed on the soil and kept in a B.O.D. chamber at a temperature of 26 ± 2ºC, without photophase. The emergence and mortality of adults for 28 days were evaluated. The results showed that the emergence of adults was lower in the treatment with M. anisopliae in sterile soil (23%). Although emergence was high in the treatment with M. anisopliae in non-sterile soil (70%), adult mortality was 98.6%. The reduction in adult survival occurred more rapidly in the treatment with M. anisopliae in sterile soil, where within 7 days all adults were dead. In the treatment with M. anisopliae in non-sterile soil, survival dropped to 25.7% at 7 days and to 14.2% at 10 days. In this study, it was demonstrated that the isolate of M. anisopliae (CPAFAP-3.8) causes mortality of immatures and adults of A. fraterculus under controlled conditions. However, field studies are still needed to assess the real potential of this microorganism for the biological control of this pest.